The effects of work-family conflict on teachers’ job satisfaction: a study in the East Coast of Malaysia - R Ibrahim, R Zirwatul Aida; Saputra, Jumadil; Rohaizad, Nor Aizal Akmal; Johar, Siti Sarawati (Primrose Hall Publishing Group, 2020)
The current study investigates the effects of work on family conflict (WFC) and family to work conflict (FWC) on job satisfaction among school teachers in Terengganu, Kelantan and Pahang, Malaysia. A questionnaire survey approach was used as a method of quantitative data collection involving 487 respondents through multistage random sampling. A Structural Equation Modelling were analysed using AMOS 25 and SPSS 25 software. The findings revealed that only FWC contributes significantly to job satisfaction. The result provides insights into the type of conflicts influencing teachers’ job satisfaction and contributes to the literature of work-family conflict, especially the study focusing on Eastern culture respondents.